Management Transformation of Organizational Behavior in Pesantren-Based Integrated Elementary Schools in the Digital Era - Rifa'i Rifa'i; Vita Fitriatul Ulya (IQRO: Journal of Islamic Education, 2026)
This study describes the transformation of organizational behavior management in pesantren-based Integral Elementary Schools (SDI) in the digital era, focusing on SDI Luqman Al-Hakim Bojonegoro. Using a qualitative case study approach with semi-structured interviews, observations, and documentation, data were analyzed using Miles, Huberman, and Saldana's interactive model. Results reveal: (1) leadership shifted from traditional-paternalistic to transformative-integrative patterns with data-driven decision making; (2) teacher work culture transformed from loose habits to a professional, measurable cyber ecosystem while maintaining Islamic brotherhood (ukhuwah Islamiyah); and (3) pesantren values such as sincerity (ikhlas), blessing (barakah), and humility (tawadhu') were reinterpreted into digital ethics (netizen akhlakul karimah). The study concludes that pesantren-based schools can achieve balanced cultural negotiations between spiritual traditions and cyber modernity.